Determination of Arctiin and Arctigenin Contents in Arctium Tomentosum Mill. by HPLC Method - Xiaoying Zhou; Haoke Zhang; Liang Ge; Haiyan Gong; Shuge Tian (E-Journal of Chemistry)
A simple, precise, rapid and accurate, binary-phase high performance liquid chromatographic method has been developed for the determination of arctiin and arctigenin contents in the Arctium tomentosumMill. with short run time. Chromatographic separation was achieved by using HPLC system, consisting of a Shimadzu LC-6AD and Kromasil C18 column (250×4.6 mm, 5 μm, with pre-column), the mobile phase consists of methanol and water (55: 45). Detection wavelength was 280 nm. The speed of flow was 1.0 mL/min. The specimen handing quantity was 10 μL. The arctiin’s linearity range was 1.575∼4.725 μg (r=0.9995). The arctigenin’s linearity range was 0.613, 3.063 μg (r = 0.9998) and the linear relationship was accurate. The average recovery (n=5) of arctiin and arctigenin were 101.55% (RSD=2.23%) 101.63% (RSD =1.49 %) respectively. The contents of arctiin and arctigenin in Arctium tomentosum Mill. were 10.69 mg/g and 0.15 mg/g, respectively. Therefore， the developed HPLC method can be applied to both in vitro studies of arctiin and arctigenin formulations as well as drug estimation in biological samples.